Current strategies for the reconstruction of the nipple-areola complex: a review - Mendizabal-Velazquez, Alondra; Granados-Romero, Juan José; Montalvo-Hernández, Jorge; Vázquez-González, Juan C.; Palacios-Rodríguez, Patricia M.; González-Martínez, Itaty C.; Brito-Brito, Nicolás R.; Abundez-Pliego, Ana L.; Valderrama-Treviño, Alan I.; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
The reconstruction of the nipple-areola complex after a mastectomy is essential for the bio-psycho-social recovery of the patient, it is generally performed 4 to 6 months after surgery and there are multiple surgical reconstruction techniques depending on the experience of the surgeon and of the individual characteristics of the patients. The most widely used for its safety and for having shown the best results is the local flap technique combined with the use of autologous, alloplastic and allograft grafts. However, currently there is still no technique that shows long-term lasting results. For this reason, in this article we describe the five categories of reconstruction techniques for the nipple-areola complex that currently exist, their advantages and disadvantages, as well as the lines of research in tissue engineering in which the world is working to find a therapeutic strategy that can reproduce a nipple-areola complex with the characteristics of the biologic.